Porcine viruses in Uganda : a study of TTSuV and PPV4 in wild and domestic pigs - Brink, Matilda (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2011)
Uganda has the largest pig population in east Africa, and most of the animals are owned by smallholders. Infectious diseases among pigs have a devastating impact on the livelihood of these farmers, which are dependent on the proceeds from pig rearing. In a metagenomics study of the wild pig species bushpig (Potamochoerus larvatus), the porcine viruses Torque teno sus virus (TTSuV) 1and 2 and Porcine parvovirus 4 (PPV4) were detected. TTSuV1 and 2 are ubiquitous in the world’s swine population, and PPV4 has been found in USA and China, but neither of them has been studied in Africa previously. The pathogenic properties of these viruses are unknown. The aim of this project was to do a first estimate of the prevalence of these viruses in pigs in Uganda, and to genetically characterize viruses detected in samples from bushpigs. The prevalence studies were made on serum samples from domestic pigs using PCR with genotype specific primers for TTSuV and PPV4 primers designed from the bushpig PPV4 sequence. Positive samples were sequenced, and phylogenetic analyses were performed in order to compare the Ugandan sequences with others already published. The prevalence of TTSuV1 and 2 in the studied domestic pigs was estimated at 16.7% and 47.9% respectively, with a co-infection of 14.6%. PPV4 was not found in domestic pigs with the bushpig primers. The bushpig TTSuV2 genome was characterized to 55% and was found to be 66-74% identical with other TTSuV2 sequences. The bushpig PPV4 genome was characterized to 70% and was 58% identical with available PPV4 sequences. Further studies must be performed to characterize the entire virus genomes from bushpig, and to evaluate the magnitude and significance of viral exchange between bushpigs and domestic pigs in Uganda.